False Cognates and Deceptive Cognates: Issues to Build Special Dictionaries - Sabino, Marilei Amadeu [UNESP]; Margalitadze, T.; Meladze, G. (Ivane Javakhishvili Tbilisi Univ Press, 2016)
A discussion is presented of the terms false cognate, false friend and deceptive cognate, usually considered synonyms, in order to establish differences between them and eliminate theoretical confusion. It is argued that the terms false cognate and deceptive cognate refer to two different linguistic phenomena. Distinct definitions are proposed for both and illustrated with practical examples, based on Set Theory. It is hoped that the discussion may be of benefit to build special dictionaries of false and deceptive cognates, as well as to improve foreign language learning and teaching methodology.
Keywords: false cognates; deceptive cognates; special dictionaries